Barriers to nutrition and physical activity participation for Australian children in foster and kinship care. (August 2021) - Green, Rachael; Savaglio, Melissa; Tate, Ruby; Morris, Heather; Breman, Rachel; Vicary, Dave; Skouteris, Helen
Highlights: Home-based carers face numerous barriers to facilitating healthy lifestyle behaviours. Upskilling carers is crucial to improving long-term health outcomes for the child/ren in their care. Training must be accessible, practical, and unique to both foster and kinship carers. Abstract: Foster and kinship carers face unique and complex challenges in caring for Australia's most vulnerable children. It is therefore necessary to ensure that home-based carers are adequately upskilled and supported to promote the health of children in their care. The aim of this paper was to better understand the barriers to developing healthy lifestyle behaviours (relevant to nutrition and physical activity) among children in home-based care, from the perspective of foster and kinship carers. Focus group sessions were conducted with 21 carers: eight foster carers and 13 kinship carers. Four key themes were identified: (1) Childhood experience and children's healthy lifestyle behaviours; (2) There are personal costs of being a carer; (3) Carers require support to develop healthy lifestyle behaviours in children; and (4) Broader systemic factors impact healthy lifestyle development. Carers in the current study described their experience of key emotional, financial, and systemic barriers to facilitating healthy lifestyle behaviours among the children in their care. To address such challenges, carers recommended the development of trauma-informed support, education, and resources to prioritise and facilitate healthy lifestyle development among children in home-based care.